Development of a SERS Probe for Selective Detection of Healthy Prostate and Malignant Prostate Cancer Cells Using ZnII. Issue 6 (15th February 2017) - Pramanik, Avijit; Chavva, Suhash Reddy; Viraka Nellore, Bhanu Priya; May, Kelli; Matthew, Tejus; Jones, Stacy; Vangara, Aruna; Ray, Paresh Chandra
Abstract: Even in the 21st century, prostate cancer remains the second leading cause of cancer‐related death for men. Since a normal prostate gland has a high Zn II content and there are huge differences in Zn II content between healthy and malignant prostate cancer cells, mobile zinc can be used as a biomarker for prostate cancer prediction. A highly efficient surface enhanced Raman spectroscopy (SERS) probe using a p ‐(imidazole)azo)benzenethiol attached gold nanoparticle as a Raman reporter, which has the capability to identify prostate cancer cells based on Zn II sensing, has been designed. A facile synthesis, characterization and evaluation of a Zn II sensing Raman probe are described. Reported data indicate that after binding with Zn II, Raman reporter attached to a gold nanoparticle forms an assembly structure, which allows selective detection of Zn II even at 100 ppt concentration. Theoretical full‐wave finite‐difference time‐domain (FDTD) simulations have been used to understand the enhancement of the SERS signal. The SERS probe is highly promising for in vivo sensing of cancer, where near‐IR light can be easily used to avoid tissue autofluorescence and to enhance tissue penetration depth. Reported data show that the SERS probe can distinguish metastatic cancer cells from normal prostate cells very easily with a sensitivity as low as 5 cancer cells mL −1 . The probe can be used as a chemical toolkit for determining mobile Zn II concentrations in biological samples. Abstract : Cancer, you cannot hide ! A highly efficient surface enhanced Raman spectroscopy (SERS) probe has been designed. The probe uses a p ‐(imidazole)azo)benzenethiol attached gold nanoparticle as a Raman reporter that has the capability to identify prostate cancer cells based on Zn II sensing.